2006
DOI: 10.1016/j.jstrokecerebrovasdis.2005.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Is Associated With Cognitive Function: The Northern Manhattan Study

Abstract: Background and purpose-Inflammation has been linked to cognitive decline and dementia but the mechanism is not clear and few studies have included Hispanic and black subjects that may be at increased risk of these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
92
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 29 publications
11
92
1
2
Order By: Relevance
“…Both were associated with executive function/processing speed domain. Our results were similar to previous studies that found a negative association between IL-6 levels and cognition (Marsland et al 2006;Wright et al 2006).…”
Section: Discussionsupporting
confidence: 93%
“…Both were associated with executive function/processing speed domain. Our results were similar to previous studies that found a negative association between IL-6 levels and cognition (Marsland et al 2006;Wright et al 2006).…”
Section: Discussionsupporting
confidence: 93%
“…In particular, these syndromes have been associated with high levels of central and peripheral IL-1 and IL-6 (21)(22)(23)(24)(25)(26), with IL-6 levels predicting subsequent cognitive decline among the elderly (24,26,27). We have recently extended these findings to show an inverse association between IL-6 and memory function among relatively healthy mid-life adults, raising the possibility that IL-6 represents a novel biomarker for risk of future cognitive decline (28).…”
Section: Introductionmentioning
confidence: 79%
“…We have recently extended these findings to show an inverse association between IL-6 and memory function among relatively healthy mid-life adults, raising the possibility that IL-6 represents a novel biomarker for risk of future cognitive decline (28). Moreover, we and others have found that observed relationships between IL-6 and cognitive function are largely independent of established risk factors for subtle and clinical cognitive impairments, including age, education, hypertension, diabetes, smoking, body mass index (BMI), and subclinical atherosclerosis (e.g., 25,28). Thus, accumulating evidence links elevated IL-6 to cognitive impairments, with animal evidence showing that hippocampal-dependent cognitive functions may be particularly vulnerable to inflammation-related processes.…”
Section: Introductionmentioning
confidence: 88%
“…Serum IL-6 levels and mental decline IL-6 has been robustly associated with cognitive function and dementia in several population-based studies (Wright et al 2006). However, data of the impact of IL-6 on cognitive decline over time are conflicting, and only a few of these prospective studies were populationbased and included the oldest old.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular mechanisms have been proposed and strongly associated with IL-6 and cognitive decline. However, Wright and coworkers suggested a direct effect on the brain because adjusting for vascular disease and subclinical atherosclerosis did not attenuate the association with cognitive decline and IL-6 (Wright et al 2006). Additionally, previous data suggest that IL-6 crosses the blood-brain barrier (BBB), and peripheral levels may represent the levels in the brain and can therefore reflect neural and systemic inflammation (Banks et al 1995).…”
Section: Gds Decline N=316mentioning
confidence: 99%